2019
DOI: 10.24198/jkp.v7i3.988
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Modality Therapy (Spiritual Deep Breathing) Resolve Student Distress

Abstract: The condition of nursing faculty students has many academic tasks such as attending classes, taking exams, socializing, adjusting to fellow students with different characteristics and backgrounds, developing talents and interests through non-academic activities. This condition causes students to not be able to manage time well so that they experience distress. Quasy experiment research used two groups pre-post-test design. The sample included 15 control groups and 15 treatment groups. The sampling technique us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…One solution to overcome health problems is by using complementary therapy, namely manipulative and bodybased therapy, such as relaxation of the respiratory system, which has benefits for & Kushariyadi, 2011). Distress conditions in a person can be treated with respiratory therapy (Kushariyadi et al, 2019).…”
Section: Diseases Department University Medicalmentioning
confidence: 99%
See 1 more Smart Citation
“…One solution to overcome health problems is by using complementary therapy, namely manipulative and bodybased therapy, such as relaxation of the respiratory system, which has benefits for & Kushariyadi, 2011). Distress conditions in a person can be treated with respiratory therapy (Kushariyadi et al, 2019).…”
Section: Diseases Department University Medicalmentioning
confidence: 99%
“…The results of other research show that using a combination of ACBT therapy with other programs or technology can provide more benefits to patients (Shen et al, 2021). The results of other research showed that ACBT therapy was accompanied by administration postural drainage in bronchitis patients it is more effective in increasing daily sputum output, increasingoxygen levels in arteries, increasing PaO2, minimizing P (A-1) compared to conventional therapy(Halim et al, 2016).The results of other research show that spiritual deep breathing therapy as a nursing modality can optimize oxygen needs in stressed cells, blood flow to the muscles decreases, whereas blood flow to the brain and skin increases, providing a feeling of warmth, comfort and calm(Kushariyadi et al, 2019). The results of lung tissue (Elsayed etVolume 3 Issue 1, February 2024, pp 90-103 https://ebsina.or.id/journals/index.php/jkmi EISSN 2502-2717 100 Active Cycle of Breathing Technique: The Right Choice for Ineffective Airway Clearance Nursing Problem al., 2015).…”
mentioning
confidence: 99%